YIELD CAPACITYOF EARLY-MATURING SOYBEAN VARIETIES DEPENDING ON SEEDING RATE - Milenko О. H.; Antonets, M. O.; Kopan, D. V.; Dobrovolskyi, S. O.; Lukina, A. R. (Scientific Progress & Innovations, 2021)
One of the strategic issues for the development of the agrarian sector and economy in Ukraine is the expansion of sown areas, increasing the yield level, raising the volume of production and improving its economic efficiency for the main grain legume crop of the world farming – soybean (Glycine max). World grain production volumes of this crop are growing rapidly, the global food security significantly depends on food products made of soybeans. Along with increasing the areas under soybean crops and expanding the variety range, the scientific substantiation and development of cultivation technology elements for varieties of this crop are of great importance. The aim of the research was to study the growth and development peculiarities and regularities of yield formation of early-maturing soybean varieties under sowing with different seeding rates. Scientific research was conducted during the period of 2019–2021. The object of the research was early-maturing varieties: ES Komandor, Samorodok and Ranok. In the field experiment, soybean varieties were sown with the following seeding rates: 700 thousand/ha; 800 thousand/ha; 900 thousand/ha and 1 million/ha. The sowing method was row method. According to our research, it was found that the variety properties and seeding rate affected the plant productivity. The maximum productivity of plants was on the variants with the seeding rate of 700 thousand seed/ha. The best weather conditions for the development of early-maturing soybean varieties were in 2019, and, accordingly, the yield level that year was the maximum compared with 2020 and 2021. On the average over the years of research, it was found that the increase in seeding rate from 700 to 900 thousand/ha resulted in the yield increase from 2.05 to 2.44 t/ha. However, further increase in seeding rate to 1 mln/ha led to the decrease in yield. The maximum yield of 2.59 t/ha was obtained in the variants of Samorodok variety. The variant of Samorodok variety, sown with the seeding rate of 900 thousand/ha ensured the highest level of production profitability – 126.22 %, according to the results of economic efficiency calculations for cultivating early-maturing soybean varieties depending on the seeding rate. For the production conditions of the Central Forest-Steppe zone, it is recommended to grow soybeans of Samorodok early-maturing variety with the seeding rate of 900 thousand /ha.